Regional-Owned Enterprise is Performance Oriented and Has an Impact on Village Development - Anhari, Sulaiman (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2023)
In the era of President Susilo Bambang Yudhoyono's leadership, the concept of village development was coined, so that there would be an even distribution of progress from upstream to downstream. Then during Jokowi Dodo's leadership, the national development scheme was focused on regional development, resulting in economic strengthening, and concrete evidence of this policy was that village funds were transferred from the center directly to the village. The aim of this policy is for villages to become the foundation for strengthening the national economy, and one of them is to give birth to regional-owned enterprise. Based on this description, this research was conducted to reveal the governance of regional-owned enterprise based on their characteristics. This research was conducted using a survey method with a quantitative approach. The research data is in the form of respondents' answers obtained from distributing questionnaires. The collected data was processed and analyzed using linear regression mathematical techniques. The research respondents were the managers of 100 regional-owned enterprise in various regions in Bima Regency, West Nusa Tenggara. The results of the study suggest that regional-owned enterprise can run well if the administrators/members have knowledge of business management. In addition, the management has good integrity, for the commitment to carry out their duties truly with a sense of responsibility. Thus, regional-owned enterprise can generate benefits that are beneficial to village economic development.